Comparison of 10-yd sprint times performed separately and embedded in a 40-yd sprint - Mann, J. B.; Mayhew, J. L. (Journal of Australian Strength and Conditioning, 2017)
Short sprints are an integral part of many field and court sports. A fundamental element of American football is the requirement of exceptional acceleration for short distances. While the 40-yd (36.6 m) sprint has been a fixture in testing for many years, more emphasis has recently been placed on evaluation of shorter sprint distances. Part of the reason may center around concern for the possibility of players incurring a hamstring strain during the execution of longer sprints. Due to the growing popularity of short sprints, many strength and conditioning specialists have begun to time both short and long sprints simultaneously. When performing both tests together the question arises as to whether the short sprint times differ when run singularly versus when they are embedded in the longer sprint. Therefore, the purpose of this study was to evaluate the difference in times for a short sprint run separately versus embedded in a longer sprint.